RECONSTRUCTION OF WOMEN’S REPRESENTATION ACT: EXPECTATIONS DAN CHALLENGES - Antonia Sasap Abao; Syarifah Ema Rahmaniah; Chainar . (Faculty of Law, Universitas Jenderal Soedirman, 2015)
This research aims to map the level of women’s representation in West Kalimantan Provincial level of parliament after the enactment of the law of women's representation. This research is a descriptive framework that was developed to reconstruct the law of gender-equitable in efforts to make the integrity election. Although the number of women who occupied the seats of West Kalimantan provincial level of parliament increased to 6 seats of the 65 seats in the 2014 election, or about 9.23%. However, the increased representation of women in parliament can not significantly be able to gives influence in the political process and existing legislation, especially to make a change in a more strategic role and gender perspective. Keywords: The representation of women, election integrity, affirmative action